SUPPORTING HOLISTIC GROWTH: THE ROLE OF TEACHERS IN DEVELOPING CHILDREN'S SOCIAL-EMOTIONAL ASPECTS IN TADIKA AL-FIKH ORCHAD MALAYSIA - Mavianti Mavianti; Rizka Harfiani; Abu Yazid Raisal; Abdurrohman Chapakiya; Nurul Zahriani Jf (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2025)
The paper aims to explore in depth how to support children's holistic development, particularly through strengthening social-emotional aspects at Tadika Al-Fikh Orchad Malaysia. This research applies a descriptive method with a qualitative approach. Data was collected through three main techniques: interviews, observation, and documentation analysis. Data analysis used a qualitative descriptive analysis method consisting of three main stages: data reduction, data presentation, and conclusion/verification. The results of the research show that the role of teachers in early childhood education has a broader scope than just teaching academic material. In Tadika Al-Fikh Orchard Malaysia, teachers act as emotional companions, role models, and facilitators in children's character building. This role is implemented through strategic approaches such as the application of teaching materials by the curriculum, Morning Circle reflective activities, emotional expression-oriented games, and stories containing moral values, showing that an approach integrated with social and emotional values can strengthen the balance of child development.